2012
DOI: 10.1007/s11064-012-0746-9
|View full text |Cite
|
Sign up to set email alerts
|

Expression Levels of the BDNF Gene and Histone Modifications Around Its Promoters in the Ventral Tegmental Area and Locus Ceruleus of Rats During Forced Abstinence from Morphine

Abstract: Brain-derived neurotrophic factor (BDNF) plays a role in mediating molecular, cellular, and behavioral adaptations underlying drug addiction. Here, we examined the influence of withdrawal from repeated morphine treatment on the expression of BDNF mRNA in the ventral tegmental area (VTA) and locus coeruleus (LC) of the rat brain. We also studied whether alternations in mRNA levels of BDNF in these tissues are associated with histone modifications around promoters II and III of the BDNF gene. Thus, chromatin imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 37 publications
3
35
0
Order By: Relevance
“…43 Other studies have reported increased expression of BDNF in the VTA following morphine withdrawal. 24 Our results provide further evidence for the role of BDNF in the acute response to morphine exposure and suggest that this may not be limited to the VTA. Catechol-Omethyltransferase (COMT) is implicated in dopamine elimination, and subsequently COMT activity reduces response to morphine 8 , while genetic variants in the COMT gene are associated with differential response to morphine as an analgesic.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…43 Other studies have reported increased expression of BDNF in the VTA following morphine withdrawal. 24 Our results provide further evidence for the role of BDNF in the acute response to morphine exposure and suggest that this may not be limited to the VTA. Catechol-Omethyltransferase (COMT) is implicated in dopamine elimination, and subsequently COMT activity reduces response to morphine 8 , while genetic variants in the COMT gene are associated with differential response to morphine as an analgesic.…”
Section: Discussionsupporting
confidence: 54%
“…In this study, we analyzed epigenetic changes in response to acute and chronic morphine induction in 10 regions of the rat brain reported to be implicated in response to opiates and the formation of addiction: the midbrain contains the VTA that has been consistently implicated in addiction 23,24 ; the pons contains the locus coeruleus that is key in the integration of opioid and stress signalling and which is served by innervation from the paraventricular nucleus of the hypothalamus 25 ; the inferior and superior colliculus regulate response to opiate withdrawal through reduced activation of mu-opioid receptor signalling 26,27 ; the cerebral cortex (containing the dorsomedial prefrontal cortex), hippocampus and cerebellum are implicated in reinforcement of drug-seeking beheaviors [28][29][30] ; the medulla oblongata is crucial in pain modulation and opiate withdrawal behaviors 31 ; and the thalamus whose function is disrupted in opiate dependence 32,33 . We measured global 5-methylcytosine and 5-hydroxymethylcytosine levels, and analyzed the DNA methylation of genes previously identified as implicated in morphine tolerance (Bdnf, Comt, Il1b, Il6, Nr3c1…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with these findings, repeated cocaine treatment in mice or ablation of the H3K9 HMT G9a in the nucleus accumbens increased mouse susceptibility to social stress, and overexpression of G9a in the nucleus accumbens rendered mice resilient to stress even after repeated cocaine treatment [124]. A recent study also reports a decrease of H3K9 trimethylation at the Bdnf promoters II and III after long-term morphine abstinence in the rat brain [138].…”
Section: G9asupporting
confidence: 59%
“…Histone acetylation is by far the most studied among histone modifications [56] . Histone acetylation includes addition of acetyl groups to lysines present in the N-terminal tails on the surface of the nucleosome, while histone deacetylation includes removal of acetyl groups ( fig.…”
Section: Histone Acetylation/deacetylationmentioning
confidence: 99%
“…Generally, the non-coding RNA binds to the complimentary sequences on the target mRNAs to repress translation, and thereby silence the gene expression [56] . The role of miRNA in alcoholism was also examined in numerous studies.…”
Section: Mirna/non-coding Rna and Alcoholismmentioning
confidence: 99%